Superplastic behavior of rosin/beeswax blends at room temperature. Issue 5 (28th August 2012) - Gaillard, Y.; Girard, M.; Monge, G.; Burr, A.; Ceretti, E. Darque; Felder, E.
Abstract Blends of rosin and beeswax were studied in terms of their thermal and mechanical behaviors. Their glass transition and α relaxation were both characterized, either by differential scanning calorimetry or by dynamic mechanical thermal analysis. In this study, we focused particularly on the impact of the microstructure on the mechanical properties, as studied by compression, shear, and nanoindentation tests. It is shown that at room temperature, these blends exhibited a viscous behavior in both the elastic and plastic regimes. From these measurements, a superplastic behavior was highlighted for blends with more than 60 wt % rosin. This superplastic behavior constitutes a real new potential in the mechanical reliability of adhesives based on rosin, which are more generally known for their very brittle behavior. As a result, it should open the way for the design of new shapes. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013